2015
DOI: 10.9755/ejfa.v27i3.19226
|View full text |Cite
|
Sign up to set email alerts
|

Low vs high and #8220;water footprint assessment and #8221; diet in milk production: A comparison between triticale and corn silage based diets

Abstract: The agriculture account is 92% of the global freshwater footprint, and 29% of this amount is used in animal husbandry to produce forage, to mix animal feed, for drinking of the animals and, at least, in the farm activities. In this trial we tested two diets whose production is characterized by different water consumption. Two homogeneous groups of milking cows were used to compare two different diets: standard feeding, with corn silage-based diet; and alternative feeding, with triticale silage-based diet. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…New Zealand has actively expanded its dairy exports to China through the construction of a free trade zone, and the dairy trade has achieved zero tariffs. The duty-paid price of New Zealand milk powder is about 1000 US dollars per ton cheaper than that of EU milk powder, and the cost of exporting to China has been reduced by an average of 13.4 percent, which gives New Zealand dairy products an overwhelming advantage in the Chinese market, making China also the largest export market for New Zealand dairy products [22,31]. It also deepens the influence of New Zealand dairy products on the balance of supply and demand in the Chinese dairy market [28].…”
Section: Comparison Of the Dairy Shares Of Australia And New Zealamentioning
confidence: 99%
“…New Zealand has actively expanded its dairy exports to China through the construction of a free trade zone, and the dairy trade has achieved zero tariffs. The duty-paid price of New Zealand milk powder is about 1000 US dollars per ton cheaper than that of EU milk powder, and the cost of exporting to China has been reduced by an average of 13.4 percent, which gives New Zealand dairy products an overwhelming advantage in the Chinese market, making China also the largest export market for New Zealand dairy products [22,31]. It also deepens the influence of New Zealand dairy products on the balance of supply and demand in the Chinese dairy market [28].…”
Section: Comparison Of the Dairy Shares Of Australia And New Zealamentioning
confidence: 99%
“…However, the contribution of the various feed stuffs to dry matter and yield should not be overlooked. For instance, corn silage which is higher contributor to the blue water footprint can be replaced with triticale silage as it has been found to have low water footprints and high contribution to milk yield [34].…”
Section: Discussionmentioning
confidence: 99%
“…Phansalkar [6] and Upali et al [7] have highlighted the crucial role of water in India's milk production. So far, most studies have explored the relationship between water and milk production by estimating the consumptive water use and further calculating water productivity in kg/m 3 [7][8][9][10]. However, these estimates do not distinguish between irrigation water from rainfall, wells, and canals, and give no assessment of the impact of different modes of water application on milk production.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that groundwater irrigation provides easy access and greater water-control to the farmers, which leads to higher crop productivity and when compared to surface irrigation like canals, tanks, etc. [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%